Reproduction of black drum (Pogonias cromis) in the Río de la Plata estuary, Argentina - Macchi, Gustavo Javier (2002)
The reproductive biology of black drum, Pogonias cromis, collected during August 1998-January 1999 from commercial catches in Samborombón Bay (Río de la Plata estuary, Argentina) was studied using macroscopic and histological analysis of the gonads. Black drums are multiple spawners with indeterminate annual fecundity that spawn from October to January. Spawning frequency, determined from the percentage of females with postovulatory follicles, ranged between 27 and 32% during the spawning peak (October-November) in 1998. At these frequencies, each female on average spawned a new batch of eggs every 3-4 days during this period. Batch fecundity was positively correlated with total length and total weight (ovary-free) and ranged between 90 000 (66 cm TL) and 2 600 000 (130 cm TL) hydrated oocytes. Relative fecundity ranged from 22 to 146 hydrated oocytes per gram of ovary-free weight.